Effectiveness of Pregnancy Awareness and its Outcomes in Women of Rural Areas of Pakistan, A Clinical Based Study - Fakharunissa, Aniqa Shahid, Qamarunissa Muhabat, Madiha Afzal, (Pakistan Journal of Medical & Health Sciences, 2022)
The aims and objectives of current study were to assess the level of awareness of pregnancy health and its outcomes among women of rural areas. In group-A, group-B and group-C the percentage of ultrasound sonography test and folic acid levels of pregnant women were showed a significant (P<0.05) changes. Similarly On evaluating the other parameters such as vaginal bleeding, abdominal pain, and pregnancy induced hypertension, gestational diabetes, gestational anemia, Hepatitis B & C, Acquired immunodeficiency syndrome (AIDS) regarding percentage standard mean deviation in different groups the results are significant(P<0.05) and remarkable changes were calculated. It was concluded in this study that public health facilities with proper heath awareness programs and increased in qualification of rural women is required for better healthy mother and child.